2003
DOI: 10.1007/s00228-003-0684-1
|View full text |Cite
|
Sign up to set email alerts
|

Absolute contraindications in relation to potential drug interactions in outpatient prescriptions: analysis of the first five million prescriptions in 1999

Abstract: Among a non-selected population of ambulatory outpatients, the number of quarterly prescriptions with contra-indications with potentially harmful drug interaction was 27 in 10,000 prescriptions. This would extrapolate to nearly 200,000 contra-indications on the same-prescription sheets in France in the first quarter of 1999.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0
3

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 27 publications
3
11
0
3
Order By: Relevance
“…Pharmacists, in particular, should avoid dispensing combinations of drugs that may have serious DDIs [32]. In the present study, only 0.4% of the patients (3/827) had contraindicated DDIs, which is similar to figures reported in studies carried out in France (0.4%) [33] and Taiwan (0.2%) [18]. A previous population-based study conducted in Brazil using the same database found a frequency of 2.4% [20].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Pharmacists, in particular, should avoid dispensing combinations of drugs that may have serious DDIs [32]. In the present study, only 0.4% of the patients (3/827) had contraindicated DDIs, which is similar to figures reported in studies carried out in France (0.4%) [33] and Taiwan (0.2%) [18]. A previous population-based study conducted in Brazil using the same database found a frequency of 2.4% [20].…”
Section: Discussionsupporting
confidence: 87%
“…Similar studies report a trend of increasing prevalence of potential DDIs with the increase in the number of drugs prescribed [11], [29], [33]. Research worldwide has shown that polypharmacy (5 or more drugs) [39] contributes to the increased risk of potential DDIs [18], [19] In the present study, approximately two fifths of the patients were taking five or more drugs.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Ils ont constaté que 27 ordonnances sur 10 000 comportaient une contre-indication absolue. Par extrapolation, ces auteurs ont estimé que pour la France, annuellement ce serait prè s de 200 000 prescriptions qui comporteraient une contre-indication absolue [7]. Avec une dé marche similaire, Malone et al ont é tudié la fré quence de 25 interactions considé ré es comme cliniquement significatives au sein d'une base de donné es provenant d'une socié té d'assurance.…”
Section: Inté Rê T Et Limites Des Systè Mes Informatisé Sunclassified
“…En France, les é tudes concernant les interactions mé dicamenteuses sont rares. Certaines ont concerné des patients traité s en ambulatoire [6,7], d'autres des ordonnances de ville qui ont é té analysé es par des mé decins ou des pharmaciens à la suite d'une hospitalisation des patients [1,[8][9][10]. La recherche et le signalement des interactions mé dicamenteuses constituent une part significative du travail du pharmacien lors de l'analyse et la validation des prescriptions.…”
unclassified